Caught in the Super-emergency - Klepec, Peter (Filozofski vestnik, 2023)
The paper proceeds in three steps. First, it addresses what urgency and emergency are in their simplest terms; then, it places this in the context of the now very popular metaphor of imprisonment, which supposedly describes what is happening to us today; and in the final steps, it presents the task of critical theory today. Starting from the distinction between urgency and emergency (the main difference being that in the latter case there is an immediate threat or danger to life, health, property, or the environment, while in the case of urgency there is no such immediate threat or danger), the paper proposes the concept of Super-emergency as a name for a (contemporary) situation that is out of control and feeds on our own antagonisms and contradictions. The accompanying atmosphere or mood is the “mood of nightmare”, which also explains why it seems so natural for us today to speak of arrest, imprisonment, or entrapment. By pointing out some consequences of prison metaphors, we suggest in the last part of the paper that it is not only urgent to think about and deal with urgency and emergency per se, but also with their particular deviation – the Super-emergency. Even if we do not have time to think and act differently, as our leaders, the media, and propaganda keep claiming (“now we do not have time to listen, to discuss, to exchange opinions, to talk”), it is precisely urgent situations that provide time for reflection and radical action to reclaim our common future. In other words, what is really urgent and necessary for us now, today, is to free ourselves from this yoke of emergency in which we are trapped and which we call here the Super-emergency.